Social appropriation of ICT and agricultural associations in the rural sector: systematic literature review 2010-2020 (2022)
Social appropriation of ICTs in rural contexts is a challenge for governments and farmers, who require ICTs to strengthen production and marketing processes through projects for inclusion and digital literacy. The purpose of this article is to analyze how this phenomenon has been studied, from what approaches or theoretical perspectives and what future approaches are needed to achieve social appropriation of ICTs in the agricultural sector. A systematic review of the literature identified four lines of research, from 2010 to 2020. The main trend is toward the study of the uses and adoption of ICTs, based on the identification of quantitative variables of use and non-use; there is also research focused on the processes of social appropriation, not only for agriculture, but also for the daily life of communities, which is where digital literacy should begin. It was possible to conclude that the line of research on social appropriation has a conceptual and methodological component that differentiates it from studies of ICT uses and adoption, because it focuses on the autonomous recognition by farmers of the benefits or weaknesses of ICT use; in addition, there is a disconnection between the identification of uses and how these can contribute to the processes of appropriation of ICTs in the agricultural sector, which imply a qualitative methodological approach and not only quantitative measurement. © 2022 Universidade Federal de Minas Gerais. All rights reserved.